Shariah Banking Soundness in Review from RGEC and Maqashid Shariah - Yusuf Faisal; Muhammad Nuryatno (International Journal of Business and Applied Economics, 2023)
This research looks at the health of Islamic banks in Indonesia with RGEC and Maqashid Shariah Performance. Population study this namely Sharia Commercial Banks registered with OJK from 2012 - 2019. namely Bank BNI Syariah, Bank BRI Syariah, Bank BCA Syariah, Bank Mandiri Syariah, Bank Syariah Bukopin , Bank Muamalat Indonesia, Bank Mega Syariah, and Bank Panin Dubai Syariah. This research resulted in a conclusion, namely the application of green governance results in better organizational performance. Tax administration system renewal resulted in decreased organizational performance. Tax administration system renewal can increase the influence of green governance on organizational performance for the better. This study adds an explanation of the performance of Islamic banks reviewed by Maqasid Shariah.